(3ZQGFH GdbQBf hQZGFH GdaQbGfs - (3fXGe GdOjf MSf Hf eMeO Hf MSjf Gdbej GdfjSGHhQj fXGe GdGYQL,J (B728 (3g` s
(3ChdgG (B:s
(3Zdi Gddg CQZH ai ZHOGY ZQGFH GdbQBf , hjaVdI GdYeje CJCgH dEjOGY QZGFH GdaQbGf hZdjg JfJgi GdCed hGdShd s
(3BNQgG (B:s
(3BNQg JaSjQ ShQI GdCfYGe s
(3GdfSNI HgG MhGTs
(3GdfUa GdChd GdBjGJ ajgG eVhHWg hbO cJHJ HGdMeQIs
(3hbhHdJ GdfSNI MSH GdWGbIs
(3YdjgG JbjjOGJ hJedcGJ s
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs